(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2026)
This work analyzes the diverse ritualistic dimensions of the Bumba Meu Boi cultural practices from Maranhão, recognized as Intangible Cultural Heritage of Humanity by UNESCO. The study distinguishes the various ritual instances that compose the Boi’s annual cycle, from the Festa Junina period until its "death" and closing in August. The research demonstrates that the ritualization of the Boi extrapolate strictly religious relations, manifesting complex syncretism and sociocultural negotiations in dialogue with the present time. To critically analyze the processes of continuity and transmission of these practices, the framework of Taylor (2003) regarding archive and repertoire is revisited, grounded in experiences of participant observation.